Estimations of child linguistic productivity controlling for vocabulary and sample size - Aguado-Orea, Javier (Frontiers in Psychology, 2022)
Children’s use of present tense suffixes is less productive than that of their parents, after correcting for sample size and lexical knowledge, according to a recently established approach for the study of inflectional productivity. This article expands on this technique by providing precise estimates of early grammatical productivity through systematic random sampling and allowing for developmental assessment. Two cross-linguistic comparisons are given in the results of this study. Two Spanish-speaking children and their parents are compared with four English-speaking children and their parents. The second comparison examines potential differences in productivity throughout developmental stages using the same six children’s speech. The findings indicate that Spanish-acquiring children are less productive than their parents while utilising the paradigm under study, but that productivity levels increase over time. In contrast, the English-speaking children’s morphosyntactic production mirrors that of their parents. Although the primary focus of this research is methodological, these findings have consequences for theoretical theories arguing either rule abstraction or a restricted generalisation of early exemplars.